2019
DOI: 10.1111/ejh.13288
|View full text |Cite
|
Sign up to set email alerts
|

A new risk model to predict time to first treatment in chronic lymphocytic leukemia based on heavy chain immunoparesis and summated free light chain

Abstract: Background Chronic lymphocytic leukemia (CLL) is frequently accompanied by immune dysregulation. Aims In this multicenter prospective study, we investigated whether heavy + light chains (HLC: IgGκ, IgGλ, IgAκ, IgAκ, IgMκ, IgMλ) and IgG subclasses (IgG1, IgG2, IgG3, and IgG4) could be used as novel prognostic markers of immunoparesis in 105 treatment‐naïve patients with CLL. Results Heavy + light chains immunoparesis of ≥1, ≥2, and ≥3 isotypes was evident in 74 (70%), 58 (55%), and 36 (34%) patients, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Patients were classified as high confidence/high risk, low confidence, and high confidence/low risk for infection. The model did not provide information regarding immunoglobulins, which is in contrast to other studies which have found that significant hypogammaglobulinemia (IgG <4g/L) or low IgG and IgA are associated with the risk of serious infection ( 58 , 59 ). Using the CLL-TIM algorithms, the occurrence of infections several years prior to the diagnosis of CLL was highly specific for the risk of infection after diagnosis but prior to CLL treatment.…”
Section: Crossovers Between Sid Pid and Autoimmunitycontrasting
confidence: 79%
See 1 more Smart Citation
“…Patients were classified as high confidence/high risk, low confidence, and high confidence/low risk for infection. The model did not provide information regarding immunoglobulins, which is in contrast to other studies which have found that significant hypogammaglobulinemia (IgG <4g/L) or low IgG and IgA are associated with the risk of serious infection ( 58 , 59 ). Using the CLL-TIM algorithms, the occurrence of infections several years prior to the diagnosis of CLL was highly specific for the risk of infection after diagnosis but prior to CLL treatment.…”
Section: Crossovers Between Sid Pid and Autoimmunitycontrasting
confidence: 79%
“…found that significant hypogammaglobulinemia (IgG <4g/L) or low IgG and IgA are associated with the risk of serious infection (58,59). Using the CLL-TIM algorithms, the occurrence of infections several years prior to the diagnosis of CLL was highly specific for the risk of infection after diagnosis but prior to CLL treatment.…”
Section: Treatment Approach For Antibody Deficiency In Sid Vs Pid Pat...mentioning
confidence: 99%
“…Thus, the model may simplify the risk stratification in clinical management. Tamar Tadmor et al proposed a new risk model based on heavy+light chains (HLC) and IgG subclasses to predict TTFT [ 104 ]. The model separated patients into 3 subgroups according to the numbers of risk factors and patients with 2 risk factors are of ultra-high-risk with a median TTFT of only 1.3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Although the association of pretreatment hypogammaglobulinemia with overall survival is uncertain, most studies including ours show clear association with stage, a marker of disease burden, and possibly duration of having CLL [8,9,23] that explained the shorter time to the first treatment in these studies. Hypogammaglobulinemia is likely a consequence of the oncogenic process of CLL since it is rarely found prior to a few years before the diagnosis [24]; however, the exact process is unknown.…”
Section: Discussionmentioning
confidence: 80%